Word from the guest editor in chief - Filipi Matutinović, Stela (Infotheca - Journal for Digital Humanities; Vol 5 No Special is (2004): Infotheca - Journal of Informatics and Librarianship, 2024)
When this special issue of Infotheca will appear, the first Tempus project in Serbia concerning academic libraries will be finished. It does not mean that all the goals concerning development of academic libraries in Serbia are achieved, but we can say that the main goal - building cooperative academic library network - is achieved, and we can even say that academic libraries together with the National Library of Serbia and the Library of Matica Srpska managed to build even broader cooperative library network than was originally planned.